First record of Coprophanaeus bellicosus (Olivier) (Coleoptera, Scarabaeidae) in a "Brejo de Altitude" forest in northeastern Brazil: a historical biogeographical approach - Silva,Fernando Augusto Barbosa (2011)
First record of Coprophanaeus bellicosus (Olivier) (Coleoptera, Scarabaeidae) in a "Brejo de Altitude" forest in northeastern Brazil: a historical biogeographical approach. This note presents the first record for a species of dung beetle of the genus Coprophanaeus, subgenus Megaphanaeus, in a "Brejo de Altitude" forest. Besides the new record, the paper discusses biogeographic aspects of the species and subgenus, as well as of the natural history of the "Brejos de Altitude", unique ecosystems in the northeast region of Brazil.